Customer Relationship Management Pada Sistem Informasi Penyewaan Lapangan Silma Sport Center - Muhammad Falah Al-Bana; Endang Retnoningsih (Journal of Students‘ Research in Computer Science, 2023)
Futsal and badminton are sports enjoyed by various groups of children, adolescents and adults. Apart from the comfortable and good field conditions, the ease factor in finding sports field information can be an advantage. In the Silma Sport Center information system for storing and managing field data and members still use it in the form of notes, information for tenants must go directly to the place and book the field. In this research, a website information system was built with the concept of Customer Relationship Management (CRM). The results of the research are in the form of a website by implementing Acquire that provides easy access to information, enhances good service, and retains listening to customers so that it can help Silma Sport Center in providing services for tenants.. Keywords: CRM, Rentals, Sports Field   Abstrak Futsal dan Bulutangkis merupakan olahraga di gemari berbagai kalangan anak-anak, remaja dan dewasa. Selain dari kondisi lapangan yang nyaman dan baik, faktor kemudahan dalam mencari informasi lapangan olahraga bisa menjadi sebuah keunggulan. Pada sistem informasi Silma Sport Center penyimpanan dan pengelolaan data lapangan serta member masih menggunakan berupa catatan, informasi untuk penyewa harus mendatangi langsung ketempat dan booking lapangan. Pada penelitian dibangun sistem informasi website dengan konsep Customer Relationship Management (CRM). Hasil dari penelitian berupa website dengan menerapkan Acquire memberikan kemudahan pengaksesan informasi, Enhance pelayanan yang baik, dan  Retain mendengarkan pelanggan sehingga dapat membantu Silma Sport Center dalam memberikan pelayanan bagi penyewa. Kata kunci: CRM, Lapangan Olahraga, Penyewaan